Crossing Gender and Colour Lines in American Fraternalism: A Study on Joseph W. Kinsley (1843–1905). (15th September 2017) - Tyssens, Jeffrey
Abstract : At first sight, Joseph W. Kinsley could be considered as one of those uncountable 'grandees' of American fraternalism whose lives have all fallen into a justified oblivion. Closer scrutiny however reveals a career within different fraternal societies that went far beyond the habitual accumulation of titles and responsibilities in the mainstream orders. Kinsley endeavoured experiments with new types of fraternities wherein the normal exclusion of women and African Americans was to be transcended, first in a frontier town in Montana, later in the federal capital. If all of these orders eventually failed, their short-lived histories nevertheless shed light on those men and women, black and white, who tried to make use of the specific context of the American west to break with segregation and gender exclusiveness. They brought this new formula to other parts of the country. Whatever the limitations of his projects and of the views that he held on race and gender, Kinsley does appear as one of the lonely pioneers who tried to break with deep-rooted fraternal orthodoxies regarding these same categories.